2017
DOI: 10.3390/ijerph14121441
|View full text |Cite
|
Sign up to set email alerts
|

The Content of Structural and Trace Elements in the Knee Joint Tissues

Abstract: Many elements are responsible for the balance in bone tissue, including those which constitute a substantial proportion of bone mass, i.e., calcium, phosphorus and magnesium, as well as minor elements such as strontium. In addition, toxic elements acquired via occupational and environmental exposure, e.g., Pb, are included in the basic bone tissue composition. The study objective was to determine the content of strontium, lead, calcium, phosphorus, sodium and magnesium in chosen components of the knee joint, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Mean concentration of Pb in the knee joint elements vary between 0.20–4 mg∙kg −1 dm [16,17]. Our study has shown that the mean concentration of this element in the infrapatellar fat pad is lower than in the bone tissue, and amounts to 0.51 mg∙kg −1 dm.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Mean concentration of Pb in the knee joint elements vary between 0.20–4 mg∙kg −1 dm [16,17]. Our study has shown that the mean concentration of this element in the infrapatellar fat pad is lower than in the bone tissue, and amounts to 0.51 mg∙kg −1 dm.…”
Section: Discussionmentioning
confidence: 76%
“…Mean level of Mg in the knee joint varies from 78 to 1600 mg∙kg −1 dm [15,16]. Our study reports the infrapatellar fat pad concentration of the element at the level of 46.57 mg∙kg −1 dm, much lower than its concentration in the bone tissue, which, because of the longer time it needs to form, may reflect chronic exposure and provide a basis for indirect assessment of the extent of environmental exposure.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Kosik-Bogacka et al ( 33 ) noticed that Pb concentrations in the anterior cruciate ligament, meniscus and cartilage were higher in men than in women, while significant difference of Pb concentration between men and women only existed in meniscus. Roczniak et al ( 40 ) noted significantly higher Pb concentrations in the femur, tibia and meniscus of men (3.22, 3.99, and 0.53 mg/kg dw, respectively) compared to women (2.41, 2.16, and 0.24 mg/kg dw, respectively). However, this study found higher Pb concentrations in the knee joint structures of women as compared to men.…”
Section: Discussionmentioning
confidence: 98%
“…The current study revealed that the level of chromium accumulated in the bone tissue was similar to its content in the connective tissue. Thus, chromium accumulation is opposite to that of cadmium [ 23 , 24 ]. In the study concerning the content of chromium in the hip joint, its level in the spongy bone was approximately 3 times higher compared to other parts of this joint.…”
Section: Discussionmentioning
confidence: 99%